Detection of Active Compounds in the Water Extract of Foeniculum Vulgare L. and Its Effects on Serum Estrogen and Prolactin Levels in Female Albino Rats - Ibrahim, Mahmood Dhannoon; Alblesh, Mohammad Adnan; Al-Sugmiany, Rafea Zaidan (Iraqi Journal of Science, 2021)
The present study was designed to estimate the active ingredients in the aqueous extract of fennel Foeniculum vulgare L. fruits and test the effects of different concentrations of the extract on serum estrogen and prolactin levels in female rats. The work was conducted to prepare the aqueous extract in the laboratory, while the secondary active substances in the extract were estimated using High-Performance Liquid Chromatography (HPLC) technology. The experiments were conducted in the animal house of the College of Science, Tikrit university,on a total of 12 adult albino virgin female rats divided into four groups, each having three rats.The aqueous extract of the fruit plant was administrated orally to animals at three concentrations (50%, 75%, and 100%) per day for 45 days. The fourth group was the control group that was left without treatment. Blood samples were obtained from the corner of the eye with a capillary tube and the serum was extracted to determine the hormone levels. The results showed that the aqueous extract of fennel fruits contains eleven active secondary metabolites, namely Eucalyptol, Terpinene, Anisole, Camphor, Anethole, Anisaldehyde, Apiole, a-pinene, Estragole, Fenchone, and Limonene, which seemed to played a role in regulating the levels of prolactin and estrogen hormones in rats treated with the extract. The results showed a direct relationship between the concentration of the fruit extract given to the animals and their serum levels of estrogen and prolactin. Increases in the levels of estrogen (44.56 ± 0.90 ng/ml) and prolactin (134.66 ± 0.80 ng/ml) were recorded using the concentration of 100% of the watery extract of Foeniculum vulgare L., as compared to the control group (126.33 ± 1.18; 6.37 ± 0.45 ng / ml, respectively). The results demonstrated the effective role of the aqueous extract of fennel fruits in stimulating estrogen and prolactin in female rats through their content of active compounds, which can be of great importance in stimulating the process of milk secretion in animals.